AgroClimate Crop Season Planning Tool: Reducing the Risk of Extreme Weather Events during Key Stages of Crop Development - Caroline G. Staub; Daniel Perondi; Diego Noleto Luz Pequeno; Patrick Troy; Michael J. Mulvaney; Calvin Perry; Brian Hayes; Willingthon Pavan; Clyde W. Fraisse (EDIS)
This 5-page publication details a new tool available to growers and Extension professionals to manage risks related to climate during seasonal planning stages. The Crop Season Planning tool is a climate-based tool that enables growers to plan planting strategies that will minimize risk to climate extremes based on historical climate data at their location. Written by Caroline G. Staub, Daniel Perondi, Diego Noleto Luz Pequeno, Patrick Troy, Michael J. Mulvaney, Calvin Perry, Brian Hayes, Willingthon Pavan, and Clyde W. Fraisse, and published by the UF/IFAS Department of Agricultural and Biological Engineering, March 2018. http://edis.ifas.ufl.edu/ae525